Representation Of Nationalism In Wonderland Indonesia Video Clip (Charles Sanders Pierce Semiotic Analysis) (International Journal of Cultural and Social Science, 2022)
The phenomenon of the decline of nationalism in Indonesia looks increasingly worrying, especially for the younger generation. This gave birth to the idea of ??Alffy Rev to make one of the video clips for Alffy Rev ft. Novia Bacmid entitled Wonderland Indonesia. The purpose of this study was to determine the representation of the sign of nationalism and to find out the expression of the meaning of nationalism in the Wonderland Indonesia video clip. This study uses a qualitative research method through the semiotic approach of Charles Sanders Peirce, in the form of a triangle theory of meaning; Representement, Object, and Interpretant, to show the sign and meaning of nationalism in the video clip. The result of this research is the message of nationalism in the music video "Wonderland Indonesia" so that the Indonesian people have a sense of commitment to Indonesia, have the courage to defend Indonesia, self-strength not to waver, purity of heart and an unyielding spirit and spirit that never dies. This video clip shows how important it is that no matter how far Indonesian youths go, the spirit of nationalism will always be present as the identity of the Indonesian people who still respect historical events and cultural heritage.